Determinan Kesenjangan Pendapatan di Propinsi Daerah Istimewa Yogyakarta - Brilliana Alviro, Annisa; Widawati, Anik Sri; Nurnilawati, Eny (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Income inequality remains a critical issue in Indonesia, aligning with Sustainable Development Goal 10, which emphasizes reducing inequality. The Special Region of Yogyakarta recorded the highest income disparity the period from 2021 to 2023, despite being know as a region with relatively high human development achievement. This study analyzes the effects of minimum wage, human development index (HDI), the number of poor people, and beneficiary families on income inequality using panel data regression. Results show that while minimum wage and beneficiary families have no significant effect. The findings suggest that development improvements have not yet ensured equitable income distribution, highlighting the need for targeted policies to sustainably reduce income inequality.